2011
DOI: 10.4103/1463-1741.77214
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a field microphone-in-real-ear approach for measuring hearing protector attenuation

Abstract: Numerous studies have shown that the reliability of using laboratory measurements to predict individual or even group hearing protector attenuation for occupationally exposed workers is quite poor. This makes it difficult to properly assign hearing protectors when one wishes to closely match attenuation to actual exposure. An alternative is the use of field-measurement methods, a number of which have been proposed and are beginning to be implemented. We examine one of those methods, namely the field microphone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 10 publications
1
38
0
1
Order By: Relevance
“…The results illustrate well the differences between the NR * and IL expressed by the TFOE, TF ext and TF canal terms in equation (2). It is expected the TF ext and TF canal terms to depend on the type of HPD [17], [20] as well as ear canal geometry.…”
Section: Attenuation Valuesmentioning
confidence: 72%
See 1 more Smart Citation
“…The results illustrate well the differences between the NR * and IL expressed by the TFOE, TF ext and TF canal terms in equation (2). It is expected the TF ext and TF canal terms to depend on the type of HPD [17], [20] as well as ear canal geometry.…”
Section: Attenuation Valuesmentioning
confidence: 72%
“…By using the sound pressure locations shown in figure 1, equation (1) (2) where P 0 is the sound pressure at the center of the head in the absence of the subject's head. The last four terms of equation (2) represent what was called above the "correction" factors relating the subjective measurements (REAT) to the objective noise reduction (NR * ).…”
Section: Basic Equationsmentioning
confidence: 99%
“…Previous research has demonstrated that the MIRE method is as uitable wayt om easure the performance of hearing protectors in situ [8]. Further,t he sound pressure at the eardrum can be accurately predicted from the response of the MIRE measurement microphone provided that the transfer function is known.…”
Section: Discussionmentioning
confidence: 93%
“…Among them, aMicrophone In Real Ear (MIRE)b ased approach appears the most effective manner to conduct field measurements, yielding to the best trade-off between speed, accuracy, repeatability and correspondence with actual practice [8].…”
Section: Introductionmentioning
confidence: 99%
“…They still obtain about 15 dB or more protection at all frequencies on average (some are of course doing worse than that), but many clearly would benefit from training and motivation for better performance. Enhanced worker training is now becoming more readily deliverable through the use of various field attenuation estimation systems (colloquially called "fit-test systems") that are being marketed today (Berger et al, 2011). …”
Section: Example 2: Exploring Subject-fit and Real-world Datamentioning
confidence: 99%